CuTiNiZrV Amorphous Alloy Foils for Vacuum Brazing of TiAl Alloy to 40Cr Steel. Issue 2 (February 2015) - Dong, Honggang; Yang, Zhonglin; Wang, Zengrui; Deng, Dewei; Dong, Chuang
<x xml:space="preserve">Abstract</x> Vacuum brazing of TiAl alloy to 40Cr steel sheets was conducted with newly developed CuTiNiZrV amorphous foils. It was found that a diffusion layer, filler metal and reaction layer existed in the brazed seam. The diffusion layer in the joint brazed with Cu43.75Ti37.5Ni6.25Zr6.25V6.25 (at.%) foil was flat and thin, containing Ti19Al6 and Ti2Cu intermetallic compounds; however, the diffusion layer brazed with Cu37.5Ti25Ni12.5Zr12.5V12.5 foil was uneven with bulges, consisting of essentially Ti-based solute solution. The foil with 12.5 at.% V showed inferior spreadability compared to that with 6.25 at.% V at brazing temperature. However, fracture happened along the diffusion layer with 6.25 at.% V foil due to the formation of brittle intermetallic phases, but the joints brazed with 12.5 at.% V foil failed through the TiAl substrate. These results show that designing amorphous alloy with less Ti and more V for brazing TiAl alloy to steel is appropriate.